SIKAP SUAMI TENTANG TANDA BAHAYA KEHAMILAN, PERSALINAN, DAN NIFAS (Perbandingan Metode Brainstorming dan Buzz Group) - Winancy winancy (Poltekkes Kemenkes Jakarta III, 2016)
The danger signs of pregnancy, childbirth, and postpartum period is important for thehusbands of pregnant wife to improve participation on preventing maternal deathscaused by the three late situations. Brainstorming dan buzz group are participatoryeducation methods which can motivate participants to be active in a discussion, shareexperience, and receive more information. The aim of this study is to know the effect ofbrainstorming and buzz group methods to husbands attitude about danger signs ofpregnancy, childbirth, and postpartum periods. This is a quasi experiment study withpretest-posttest non randomized design. The Population in this study was husbans ofpregnant wife in Puskesmas Sukamakmur Subdistrict of Bogor District especiallySirnajaya and Cibadak village. Sampling was conducted using accidental sampling anddevided into two groups, the brainstorming group with 63 respondent and buzz groupwith 61 respondents. The results showed that the respondents attitude was alsoimproved significantly with p <0.005 in brainstorming group and p<0.001 in buzzgroup. The results of Mann-Whitney test described that the increased median valueattitude of the respondents in buzz group was better than brainstorming group. Fromthis study it can be concluded that health education with brainstorming methods andbuzz groups have significant effect on attitudes husband of pregnant women aboutdanger signs of pregnancy, childbirth, and postpartum. Effect of buzz group method wasbetter to improve the median value of knowledge and attitudes than brainstormingmethods.